Formation of a Complex between Nucleolin and Replication Protein a after Cell Stress Prevents Initiation of DNA Replication - Daniely, Yaron (The Rockefeller University Press, 2000)
We used a biochemical screen to identify nucleolin, a key factor in ribosome biogenesis, as a high-affinity binding partner for the heterotrimeric human replication protein A (hRPA). Binding studies in vitro demonstrated that the two proteins physically interact, with nucleolin using an unusual contact with the small hRPA subunit. Nucleolin significantly inhibited both simian virus 40 (SV-40) origin unwinding and SV-40 DNA replication in vitro, likely by nucleolin preventing hRPA from productive interaction with the SV-40 initiation complex. In vivo, use of epifluorescence and confocal microscopy showed that heat shock caused a dramatic redistribution of nucleolin from the nucleolus to the nucleoplasm. Nucleolin relocalization was concomitant with a tenfold increase in nucleolin–hRPA complex formation. The relocalized nucleolin significantly overlapped with the position of hRPA, but only poorly with sites of ongoing DNA synthesis. We suggest that the induced nucleolin–hRPA interaction signifies a novel mechanism that represses chromosomal replication after cell stress.